Maternal appraisal, social support and parenting stress among mothers of children with cerebral palsy - Ang, Grace Hui En; Juhari, Rumaya (International Journal of Children, Women, Elderly and Disable People, 2017)
Caring for individuals with disabilities can be a heavy responsibility that may evoke stress among caregivers. Hence, the main purpose of this study was to determine the relationships between maternal appraisal, social support and parenting stress among mothers of children with cerebral palsy in Selangor, Malaysia. The data were collected through self-administered questionnaire with the participation of a total of 42 mothers of children with cerebral palsy. Family Impact of Child Disability Scale (Trute, Hiebert-Murphy, Benzies, & Levine, 2009) was used to determine maternal appraisal, while perceived social support among the respondents was measured with Multidimensional Scale of Perceived Social Support (Zimet et al., 1988). Maternal parenting stress was determined using Parental Stress Scale (Berry & Jones, 1995). The findings of this study demonstrated the significant relationships between maternal appraisal and parenting stress, whereby negative appraisal and parenting stress were positively correlated, while mothers’ positive appraisal correlated negatively with parenting stress. Similar negative correlation was also identified between perceived social support and parenting stress. Apparently, the findings imply that maternal appraisal plays a significant role in determining parenting stress among mothers of children with cerebral palsy. In specific, negative appraisal was found to be the strongest predictor of maternal parenting stress. Findings of this study suggest of the importance of boosting positive appraisal and preventing negative appraisal as measures in reducing the maternal parenting stress among these mothers. It is recommended for future research to take into account the caregiving role of fathers for children with cerebral palsy in attempt to better understand the parenting well-being of such parents.